IMPACT ON CAPITAL STRUCTURE DECISION MAKING: INDIAN MEDIUM-SIZED FOOD INDUSTRY ANALYSIS - Aggarwal, Ansita; Acharya, Satya Ranjan (Copernican Journal of Finance & Accounting, 2020)
This paper seeks to investigate the relationship between equity and factors affecting them in Indian medium-sized food industry. The analysis has been done on medium-sized firms of food industry taken from prowess software. The data of 5 years has been taken from 2013-2017 so as to get a clear view of analysis over the period of time. Regression analysis is used in the estimation of functions related to equity with a measure of capital structure. The results reveal a significant positive relationship of tangible fixed assets and growth opportunities with equity, significant negative relationship of age, profitability, tax provision and total assets with equity. The research suggests that medium-sized food firms of food industry rely more on debt than equity.